Diagnostic Accuracy of MRI Myelogram in Cases of Spinal Stenosis, Keeping Neurosurgical Findings as a Gold Standard - Bibi, Ayesha; Shoukat, Shaista; Shahbaz, Sumera; Bibi, Zakia; Samad, Abdul; Magsi, Farah (Biological and Clinical Sciences Research Journal, 2025)
Lumbar spinal stenosis (LSS) is a prevalent condition associated with neurogenic claudication and radiculopathy, often requiring surgical intervention for definitive management. While conventional MRI is commonly used, MRI myelography offers a non-invasive, contrast-free alternative that may improve diagnostic accuracy. However, its reliability against intraoperative neurosurgical findings, the gold standard, requires validation. Objective: The present study aims to evaluate the diagnostic accuracy of MRI myelogram in detecting spinal stenosis, keeping neurosurgical findings as the gold standard, in patients presenting to a tertiary care hospital in Pakistan. Methods: After the ethical approval from the institutional review board, this cross-sectional study was conducted at the Department of Radiology & Department of Neurosurgery, Jinnah Postgraduate Medical Centre, Karachi from 03/December/2024 to 03/February/2025. Through non-probability consecutive sampling, 123 patients aged 18 years or older, of either gender, presenting with symptoms of spinal stenosis (e.g., neurogenic claudication, radiculopathy, or myelopathy), undergoing MRI myelogram followed by neurosurgical evaluation or intervention, were included in the present study. Results: The sensitivity of MRI myelography for diagnosing spinal stenosis was found to be 91.80%, indicating its strong ability to detect actual positive cases. The specificity was calculated at 87.27%, reflecting its reliability in correctly identifying negative cases. The ROC curve analysis with an AUC of 0.89 of MRI myelography findings in predicting LSS, taking intraoperative neurosurgical findings as the gold standard. Conclusion: MRI myelography is an extremely sensitive imaging technique requiring minimal intervention to diagnose lumbar spinal stenosis.